AB0615 Changes in somatosensory evoked potentials in patients with primary sjogren's syndrome. (12th June 2018) - Dziadkowiak, E.; Sebastian, A.; Wieczorek, M.; Kusińska, E.; Waliszewska-Prosół, M.; Wiland, P.; Ejma, M.
Abstract : Background: Primary Sjogren's syndrom (pSS) is a chronic autoimmune disease, which, in addition to impaired function of exocrine glands, can affect other organs including nervous system. Objectives: The aim of the study was to establish whether in patients with pSS without central nervous system (CNS) involvement, the function of the central portion of the sensory pathway can be challenged. Methods: In 33 patients diagnosed with pSS without clinical features of CNS damage and normal head CT scan, somatosensory evoked potentials (SEP) were studied. The results were compared to other clinical parameters of the disease, particularly to immunological status. The control group consisted of 20 healthy volunteers selected with respect to age and sex. Results: Mean latency of all components of SEP were considerably prolonged in patients compared to the control group. Mean interpeak latency N20-N13 (duration of central conduction TT) did not differ significantly between the groups. However, in the study group, mean amplitude of N20P22 and N13P16 was significantly higher compared to healthy individuals. In patients with PSS, significant differences in SEP parameters depending on duration of the disease, duration of arthralgia and presence of SSA and SSB antibodies were noted. No significant differences in mean SEP parameters were observed with respect to skin lesions, xerophthalmia, current joint pain and swelling, focus score, levels of C3 and C4 complement components, ESR, CRP and presence of Ro52 antibodies. Conclusions: The authors confirmed central nervous system involvement often observed in patients with pSS. They also showed dysfunction of the central sensory neuron as a difference in amplitude of cortical response, which indicates subclinical damage to the CNS. Disclosure of Interest: None declared